Decision Support System For Selection Of Electric Light Ball For Household With Technique Method For Order Preference By Simillarity To Ideal Solution (Topsis) - Pandi Barita Nauli Simangunsong; Paska Marto Hasugian; Makmur Tarigan (Sean Institute, 2021)
In the selection of these light bulbs, users are often confused with the choice of light bulbs that are so widely circulated in the market, ranging from brands, types, quality, prices that continue to compete and with other advantages on offer often make users confused to get Energy efficient light bulbs at affordable prices and with the best quality. The problem doesn't just stop there when placing light bulbs in each room of the house also often gets into trouble. The problem that is often caused is mismatch, this usually happens when the light bulb has been placed. The wattage capacity of the light bulb often does not match the size of the room, resulting in less than optimal lighting. Watt capacity or large power consumption sometimes also does not guarantee to be able to get good lighting. Therefore we need a decision support system that can calculate values ​​to be able to help users determine the desired light bulb properly and precisely according to needs. This decision support system implements the technique for order preference by simillarity to ideal solution (TOPSIS) method, which is a method that can give weighting and ranking for each criterion. With the technique for order preference by simillarity to ideal solution (TOPSIS) method, the author creates a system that is expected to later be able to assist decision making in the selection of electric light bulbs.